How Lithuanian language textbooks present language to gymnasium pupils - Urbonaitė, Daina (Taikomoji kalbotyra, 2019)
The article analyses, how the Lithuanian school education system teaches to understand language and evaluate linguistic phenomena (linguistic diversity, different language forms and varieties) as well as language functions (communicative and function of identity). Basis of the research are the newest Lithuanian language textbooks for the last two gymnasium grades (11-12th grades), published since year 2000. Using qualitative analysis method it is being investigated, what notion of language is presented to the pupils, how much the descriptive approach to language of contemporary linguistics and knowledge about language are present in the textbooks, and to what extent there still exist attitude of the so-called traditional (prescriptive) grammar and ideas of language corrections. Language teaching at school serves double function – on the one hand, school teaches literacy, where language is understood as a tool for creation and analysing of texts. On the other hand, language in itself is a study object, about which pupils at school receive a certain understanding. Therefore, the question arises, what notion of language is being formed in the Lithuanian education system on the gymnasium level through teaching material – Lithuanian (native) language textbooks. Does the teaching material for the last two – 11-12th – grades provide knowledge about language of contemporary science, as it might be expected in the education of the 21st century? Do the pupils get introduced to science-based notion of language, as it is accepted in current linguistics, which is a descriptive science, that seeks to study and describe all the aspects of a language descriptively, based on facts, without prejudices and evaluations. Or is it on the contrary being followed the notion of language, which is characteristic of normativity and prescriptivism and which is rejected by contemporary linguistics as not scientific. The research analyses five Lithuanian language textbooks for 11-12th grades, published after year 2000, which have been selected for the analysis using the database of textbooks and other teaching materials (https://www.emokykla.lt/bendrasis/mokykis/vadoveliu-db/naujausi-vadoveliai). The main question, that is being raised with this research, is whether and to what extent scientific or non-scientific notion of language is being formed in school language textbooks, what attitude is predominant, and which notion of language is prevalent, if different attitudes exist. The method of the research is qualitative discourse analysis of the textbooks, using the qualitative data analysis program NVivo. The results of the textbooks’ analysis show, that non-scientific notion of language is dominant in the Lithuanian education system. The majority of the analysed textbooks represent this notion. The main characteristics of this notion, visible in the textbooks, are prescriptivism, romantic images of language, ideology of linguistic nationalism. However, besides the dominant normative approach to language, the scientific, descriptive approach is also visible in the textbooks, though to a lesser extent than the normative approach. One of the analysed textbooks is different from the rest ones with its exceptionally descriptive approach to language as a study object.